2016
DOI: 10.1186/s41479-016-0021-y
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis and pneumonia in HIV-infected children: an overview

Abstract: Pneumonia remains the most common cause of hospitalization and the most important cause of death in young children. In high human immunodeficiency virus (HIV)-burden settings, HIV-infected children carry a high burden of lower respiratory tract infection from common respiratory viruses, bacteria and Mycobacterium tuberculosis. In addition, Pneumocystis jirovecii and cytomegalovirus are important opportunistic pathogens. As the vertical transmission risk of HIV decreases and access to antiretroviral therapy inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 100 publications
0
25
0
Order By: Relevance
“…[83] Although there is considerable difficulty estimating the association between HIV and pulmonary tuberculosis (PTB) in African children, the epidemiology of childhood TB and HIV overlap considerably. [84,85] Routine programmatic data from Cape Town prior to the paediatric ART roll-out reported a TB incidence of 1 596 per 100 000 [86] in CLHIV, decreasing considerably following ART access, [87,88] and linked also to a reduction in associated hospitalisations. [89] HIV infection associated with multidrug-resistant (MDR) paediatric TB is a challenge, and SA studies reported a paediatric HIV prevalence of 54%, 77% and 43% amongst children with MDR TB in Johannesburg, KwaZulu-Natal and Cape Town, Western Cape in 2008, 2009 -2010 and 2003 -2008 respectively.…”
Section: Respiratory-related Morbidity and Mortalitymentioning
confidence: 99%
“…[83] Although there is considerable difficulty estimating the association between HIV and pulmonary tuberculosis (PTB) in African children, the epidemiology of childhood TB and HIV overlap considerably. [84,85] Routine programmatic data from Cape Town prior to the paediatric ART roll-out reported a TB incidence of 1 596 per 100 000 [86] in CLHIV, decreasing considerably following ART access, [87,88] and linked also to a reduction in associated hospitalisations. [89] HIV infection associated with multidrug-resistant (MDR) paediatric TB is a challenge, and SA studies reported a paediatric HIV prevalence of 54%, 77% and 43% amongst children with MDR TB in Johannesburg, KwaZulu-Natal and Cape Town, Western Cape in 2008, 2009 -2010 and 2003 -2008 respectively.…”
Section: Respiratory-related Morbidity and Mortalitymentioning
confidence: 99%
“…It is acute respiratory tract infection that causes inflammation in the alveoli of lungs resulting in accumulation of pus and fluid, which lead to difficulty in breathing. Pneumonia mainly affects younger children as compared to adults causing annually 0.68–0.92 million deaths in children worldwide . Tuberculosis on the other hand is caused by the Mycobacterium tuberculosis , which mostly affects the lungs, causing lung tuberculosis or pulmonary tuberculosis.…”
Section: Introductionmentioning
confidence: 99%
“…Tuberculosis is a dreadful infection in developing countries especially in African and Asian continents, probably due to their insufficient means for its treatment. Tuberculosis infects 9 million people mostly children every year, which leads to approximately 2 million deaths annually . These statistics related to pneumonia and tuberculosis deaths are likely to increase in future due to human immunodeficiency virus (HIV) infection and spread of multidrug‐resistant bacterial strains…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations